(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
La Squisito serves a unique variety of toppings and ingredients, unlike the other pizza’s company. The business has the capacity to widen its market because of its unique products at a reasonable price. The ultimate aim of marketing is the exchange of goods and services from producers to consumers. The proponents did not only aim to give a good quality of foods yet they also aim to give a great experience and satisfaction to guests/consumers. The researchers used a survey method with 50 respondents. The respondents were asked different questions with regard to the desired product. A formal list of the questionnaire is prepared by the researchers and distributed to the respondents near in the vicinity. The gathered data served as a basis for enhancing the proposed business product. The respondents who participated in the survey gave their positive comments and recommendation on the proposed business product and its location. Data gathered served as basis for the improvement of such: flavors, ingredients, and price of the product. In some instances, the voice of the interviewees gives a great impact on the innovation of the product. La Squisito can ably delegate the application of knowledge and skills to the staffs/employees, management, recruitment and management of intellectual property. The researchers found out that the product had large success rate especially in its strategically location, In line with this, They concluded that the business will be able to gain back a 100% investment if they are able to sell 80 servings each of the product a day. The researchers kept on promising their products through the use of social media and created their own page to let prospect customers see the product line herein business is made possible.